PELATIHAN BANTUAN HIDUP DASAR UNTUK MENINGKATKAN KESIAPSIAGAAN DAN KEBERANIAN SISWA SMA AL-FITYAN MEDAN - Damanik, Balqis Nurmauli; Syahferi Anwar; Tanjung, Dudut; Ismayadi, Ismayadi; Nilawati; Manurung, Irma Valentina (Jurnal Pengabdian Masyarakat Sapangambei Manoktok Hitei, 2024)
Abstract The incidence of respiratory arrest and cardiac arrest in the community is closely related to the epidemiology of heart disease. According to data from the Indonesian Ministry of Health in 2024, the prevalence of heart disease in Indonesia is 17 per 1000 people, increasing the risk of unpredictable occurrences of cardiac arrest and respiratory arrest. Adolescents, as members of both family and community, must possess basic skills in providing basic life support (BLS) to reduce the risk of death complications due to heart disease. The objectives of the BLS training conducted at SMA Al-Fityan Medan are to (1) provide health education on heart disease to adolescents, (2) teach adolescents their role in daily life to reduce the risk of heart disease from an early age, and (3) provide BLS training to adolescents. This community service activity (PKM) includes health education and a BLS demonstration. The training proved beneficial, with a significant increase in participants’ knowledge, as evidenced by comparing pre-test and post-test results (p<.000). Participants were also able to effectively perform BLS after the training. Education on heart disease and BLS training for adolescents is essential in preventing heart disease and its complications. Keywords: basic life support, adolescent, cardiovascular, SMA Al-Fityan Medan